2013
DOI: 10.1109/jdt.2012.2236300
|View full text |Cite
|
Sign up to set email alerts
|

A GaN-Based LED With Perpendicular Structure Fabricated on a ZnO Substrate by MOCVD

Abstract: A perpendicular InGaN/GaN multiple-quantumwells structure on ZnO substrate for blue light emitting diode (LED) was successfully fabricated by use of Metal-organic Chemical Vapor Deposition (MOCVD). During the growing process of GaN-based materials on ZnO substrates, the low-temperature-grown GaN buffer layer, inserted between ZnO substrate and undoped GaN layer, prevented the Zn and O from diffusing from ZnO substrate into the n-GaN layer. This thin GaN buffer layer, mainly as a insulating layer, was grown at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The availability of a relaxed InGaN buffer layer with a lattice parameter closer to that of the QWs is hence highly desirable to obtain high efficiency long wavelength (>500 nm) III-N LEDs or lasers. Attempts have been made to fabricate as-grown relaxed InGaN buffers on substrates such as ZnO [11][12][13] and ScAlMgO 4 [14,15]; however, the very low growth temperatures required for deposition on ZnO and the high n-type conductivity of InGaN grown on ScAlMgO 4 substrates have made metal-organic chemical vapor deposition (MOCVD) growth efforts on these substrates very challenging. Alternately, partially relaxed engineered InGaN substrates have been explored [6] and relaxed InGaN buffer layers have been fabricated by molecular-beam epitaxy (MBE) and used as pseudo substrates for MOCVD growth [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a relaxed InGaN buffer layer with a lattice parameter closer to that of the QWs is hence highly desirable to obtain high efficiency long wavelength (>500 nm) III-N LEDs or lasers. Attempts have been made to fabricate as-grown relaxed InGaN buffers on substrates such as ZnO [11][12][13] and ScAlMgO 4 [14,15]; however, the very low growth temperatures required for deposition on ZnO and the high n-type conductivity of InGaN grown on ScAlMgO 4 substrates have made metal-organic chemical vapor deposition (MOCVD) growth efforts on these substrates very challenging. Alternately, partially relaxed engineered InGaN substrates have been explored [6] and relaxed InGaN buffer layers have been fabricated by molecular-beam epitaxy (MBE) and used as pseudo substrates for MOCVD growth [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gallium nitride-(GaN-) based materials, with a wide band gap, have recently attracted great attention because of their wide applications in advanced optoelectronic devices [18][19][20]. Besides physics applications, there is an increasing interest in electrochemistry field due to their unique physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression methods include a low growth temperature, 16 Al 2 O 3 passivation, 17 and nitrogen carrier gas. 18 On the other hand, we have demonstrated that ScAlMgO 4 (0001) substrates are chemically stable at growth temperatures of GaN (∼1000 • C). 20 In addition, we have established the growth conditions of In y Ga 1−y N (y ∼ 0.17) templates on lattice-matched ScAlMgO 4 (0001) 20 and, demonstrated that In x Ga 1−x N/In y Ga 1−y N QWs on In y Ga 1−y N/ScAlMgO 4 templates emit in the red spectral range.…”
Section: Introductionmentioning
confidence: 90%
“…[9][10][11][12][13][14][15] However, In y Ga 1−y N thick layers are typically grown on foreign templates such as GaN on sapphire and involve numerous threading dislocations. One way to avoid the lattice mismatch between In y Ga 1−y N and the underlying template is to use a substrate lattice-matched to In y Ga 1−y N. Toward this end, ZnO [16][17][18] and ScAlMgO 4 [19][20][21][22][23][24][25][26] are attractive as their a-lattice parameters match those of In 0.18 Ga 0.82 N and In 0.17 Ga 0.83 N, respectively. However, for ZnO substrates, interfacial reactions during the growth of nitride semiconductors must be suppressed.…”
Section: Introductionmentioning
confidence: 99%